Evaluation of realized investments in agriculture in the Carpathian region in Serbia - Jonel Subić; Vesna Popović; Svetlana Roljević (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Central transition phase, in which there is Serbia, represents a radical turning point in the future development, not only agriculture, but the overall national economy and all of its participants. Consequently, investment in new economic subjects (companies and farms), recapitalization of existing subjects (companies and farms) and the consolidation of the financial system can greatly accelerate the development of a market economy in our country. However, a large number of economic subjects (companies and farms) have negative business performance, reflected in the reduction of market share and profitability, growth of indebtedness, inadequate investment and increased volume of diversified business activities at the expense of the primary job. Also, although the upward trend registered investments, macroeconomic indicators of investment trends indicate a high risk investment, both in agricultural estates, as well as companies from other industries. Imposes a dynamic investment risk reduction, which would increase the attractiveness of investment and stimulate domestic and foreign investors to evaluate various combinations of risk and return. Given the perspective of the enlargement of the European Union, resulting in Serbia, as well as the fact that in the future development of our farm investment activity to occupy a crucial place, the survey focused on the evaluation of investments in agriculture in the Carpathian region in Serbia.
Keywords: 330; investments; agriculture; Carpathian region; Serbia